School Well-Being of Elementary School Children: Motivational and Educational Predictors - Gordeeva T.O; Sychev O.A; Lunkina M.V (Moscow State University of Psychology and Education, 2019)
The goals of modern education go beyond mastering cognitive skills, competencies and knowledge. An equally important result of education is the child's school well-being, his/her positive attitude towards school, learning, teachers, and his/her own potential. This study is dedicated to the exploration of internal and external predictors of well-being in Russian elementary schoolchildren (N=1006).It assesses the impact of the learning system (developmental/traditional), satisfaction with relationships with teachers, and intrinsic and extrinsic types of academic motivation on school well-being and academic self-esteem. The results of the study show that the well-being of elementary schoolchildren is based on the positive impact of intrinsic and autonomous motivation and the negative impact of external motivation based on control and demands of teachers and parents. The results also show that the child's relationship with the teacher and perception of him/her as an interesting person, ready to help and support in the learning process, play an important role in the child's school well-being and intrinsic motivation. The results of structural equation modeling (SEM) confirm that developmental education programs, in comparison with traditional ones, also contribute to school well-being and academic self-esteem of elementary schoolchildren. The practical significance of the study is to take into account the role of both pedagogical (the role of the teacher's personality and the teaching system) and psychological factors (intrinsic and extrinsic motivation) in maintaining the well-being of elementary schoolchildren.